Impact of pre-drying and frying time on physical properties and sensorial acceptability of fried potato chips - Cruz G. (2018)
The authors are grateful to Cienciactiva for the M.L. Rojas Ph.D. (CONCYTEC, Peru; Contract 087-2016-FONDECYT) scholarship, from the ‘‘Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica”.